Homoarginine and all‐cause mortality: A systematic review and meta‐analysis. (14th June 2018) - Zinellu, Angelo; Paliogiannis, Panagiotis; Carru, Ciriaco; Mangoni, Arduino A.
Abstract: Background: Homoarginine, a basic amino acid and analogue of L‐arginine, has been shown to exert salutary effects on vascular homoeostasis, possibly through interaction with the enzymes nitric oxide synthase and arginase. This might translate into improved survival outcomes, particularly in subjects with moderate‐high cardiovascular risk. We conducted a systematic review and meta‐analysis to investigate the association between circulating homoarginine concentrations and all‐cause mortality in observational studies of human cohorts. Materials and methods: Studies reporting baseline circulating homoarginine concentrations and all‐cause mortality as outcome were searched using the MEDLINE, Scopus and Cochrane databases until January 2018. Hazard ratios (HRs) with 95% confidence intervals (CIs) derived from multivariate Cox's proportional‐hazards analysis were extracted from individual studies. Results: A total of 13 studies in 11 964 participants were included in the final analysis. Homoarginine concentrations were inversely associated with all‐cause mortality (HR 0.64, 95% CI 0.57‐0.73). This association remained significant in participant sub‐groups with predominant cardiovascular disease (HR 0.64, 95% CI 0.55‐0.76) and renal disease (HR 0.60, 95% CI 0.46‐0.68). Conclusions: This meta‐analysis of observational studies showed an inverse association between circulating homoarginine concentrations and all‐cause mortality. Further research is warranted to investigate the direct effects of homoarginine on cardiovascular homoeostasis, the associations between homoarginine and all‐cause mortality in other population groups, and the effects of interventions on homoarginine concentrations on clinical outcomes.